From the stomach to locus coeruleus: new neural substrate for ghrelin’s effects on ingestive, motivated and anxiety-like behaviors - Maric, Ivana; López-Ferreras, Lorena; Bhat, Yashaswini; Asker, Mohammed; Börchers, Stina; Bellfy, Lauren; Byun, Suyeun; Kwapis, Janine L.; Skibicka, Karolina P. (Frontiers in Pharmacology, 2023)
Ghrelin, a stomach-derived orexigenic hormone, has a well-established role in energy homeostasis, food reward, and emotionality. Noradrenergic neurons of the locus coeruleus (LC) are known to play an important role in arousal, emotion, cognition, but recently have also been implicated in control of feeding behavior. Ghrelin receptors (the growth hormone secretagogue receptor, GHSR) may be found in the LC, but the behavioral effects of ghrelin signaling in this area are still unexplored. Here, we first determined whether GHSR are present in the LC, and demonstrate that GHSR are expressed on noradrenergic neurons in both sexes. We next investigated whether ghrelin controls ingestive and motivated behaviors as well as anxiety-like behavior by acting in the LC. To pursue this idea, we examined the effects of LC GHSR stimulation and blockade on food intake, operant responding for a palatable food reward and, anxiety-like behavior in the open field (OF) and acoustic startle response (ASR) tests in male and female rats. Our results demonstrate that intra-LC ghrelin administration increases chow intake and motivated behavior for sucrose in both sexes. Additionally, females, but not males, exhibited a potent anxiolytic response in the ASR. In order to determine whether activation of GHSR in the LC was necessary for feeding and anxiety behavior control, we utilized liver-expressed antimicrobial peptide 2 (LEAP2), a newly identified endogenous GHSR antagonist. LEAP2 delivered specifically into the LC was sufficient to reduce fasting-induced chow hyperphagia, and to decrease the motivation to work for a sugar reward; this effect had a shorter latency and was more persistent in females compared to males. Moreover, blockade of GHSR in the LC increased anxiety-like behavior measured in the ASR test in both sexes. Taken together, these results indicate that ghrelin acts in the LC to alter ingestive, motivated and anxiety-like behaviors, with a degree of sex divergence.